Laminae Camels from the Late Miocene (Early Hemphillian) of the Curré Formation, San Gerardo de Limoncito, Coto Brus Canton, Puntarenas Province, Costa Rica - Laurito, César A. (2016)
This work describes abundant fossil remains of a species of lamine camel, recovered from the San Gerardo de Limoncito local fauna in southern Costa Rica. The material corresponds to dental pieces and postcranial bones of Hemiauchenia vera Matthew, 1909 species, which is basically recognized by the biometry of the astragali and the anterior phalanx I, besides dental morphology. This new fossil record also permits to accurate the biochronologic age of the outcrop and its correlation with other Early Hemphillian localities of North America.